RECONSTRUCTING THE LEARNING PARADIGM OF ISLAMIC RELIGIOUS EDUCATION BASED ON PROBLEM-BASED LEARNING FROM THE PERSPECTIVE OF ISLAMIC EDUCATIONAL PHILOSOPHY. - Sutiono, Sutiono; Saleem, Rizwana (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2026)
Islamic Religious Education (IRE) plays a strategic role in shaping learners’ intellectual, moral, and spiritual character. However, contemporary IRE learning practices remain largely dominated by teacher-centered and text-based approaches, resulting in a gap between the normative objectives of Islamic education and its pedagogical implementation. This study aims to reconstruct the learning paradigm of Islamic Religious Education by integrating Problem-Based Learning (PBL) within the framework of Islamic educational philosophy. Employing a qualitative-conceptual approach through philosophical analysis, this article examines IRE learning from ontological, epistemological, and axiological perspectives grounded in Islamic thought. The analysis draws upon classical and contemporary Islamic educational concepts, including ta’dīb, tazkiyah al-nafs, tauḥīd, ijtihād, tafakkur, and tadabbur, and aligns them with the core principles of Problem-Based Learning. The findings indicate that PBL, when reconstructed through Islamic educational philosophy, transcends its methodological function and becomes an integrative pedagogical paradigm that harmonizes critical thinking with spiritual consciousness. This reconstructed paradigm positions learners as active meaning-makers while maintaining Islamic moral and spiritual orientations, and redefines teachers as murabbī and mu’addib who guide intellectual inquiry and spiritual reflection. The study concludes that an integrative PBL-based IRE paradigm offers a holistic, contextual, and transformative learning model capable of fostering intellectual competence, ethical awareness, and spiritual maturity in accordance with Islamic educational ideals. This research contributes theoretically to the development of Islamic education pedagogy that is philosophically grounded and responsive to the challenges of twenty-first-century education.